Radiographic Markers of Femoroacetabular Impingement: Correlation of Herniation Pit and Femoral Bump with a Positive Cross-Over Ratio - Max J. Scheyerer; Carol E. Copeland; Jeffrey Stromberg; Thomas Ruckstuhl; Clément M. L. Werner (Advances in Orthopedics)
Introduction. The goal of this study was to research the association of femoral bumps and herniation pits with the overlap-ratio of the cross-over sign. Methods. Pelvic X-rays and CT-scans of 2925 patients with good assessment of the anterior and the posterior acetabular wall and absence of neutral pelvic tilt were enrolled in the investigation. Finally pelvic X-rays were assessed for the presence of a positive cross-over sign, and CT-scans for a femoral bump or a herniation pit. Additionally, if a positive cross-over sign was discovered, the overlap-ratio was calculated. Results. A femoral bump was found in 53.3% (n=1559), and a herniation pit in 27.2% (n=796) of all hips. The overlap-ratio correlated positively with the presence of a femoral bump, while a negative correlation between the overlap-ratio and the presence of a herniation pit was found. The latter was significantly more often combined with a femoral bump than without. Conclusions. We detected an increased prevalence of femoral bump with increasing overlap-ratios of the cross-over sign indicating a relation to biomechanical stress. The observed decreased prevalence of herniation pits with increasing overlap-ratios could be explained by reduced mechanical stress due to nontightened iliofemoral ligament in the presence of retroversion of the acetabulum.